Thermal and Electrical Analysis of Solid Aluminium Capacitors. (1987) - Dekker, E. H.L.J.; Lasance, C. J.M.
Abstract : The thermal properties of electronic components partly determine the reliability of electronic equipment. For electrolytic capacitors, they also set the limits for the ripple current and voltage values. This article first discusses the voltage limits under various conditions of temperature, frequency and polarity. Then the connection of ripple current to these parameters and to the capacitor's resistance is treated. An extensive analysis is made of the influence of heat conduction in the capacitor and the printed-circuit board, for metal-cased as well as for epoxy-coated pearl types. The study pays particular attention to solid aluminium capacitors containing a manganese dioxide semiconductor. They have some extraordinary properties: a temperature range of at least – 80 to + 175℃, and an appreciable reverse voltage potential.These can be fully employed to improve the ripple-current specification.